Business process reengineering of the IT helpdesk with ARIS Toolset Release 6.0 : the case of VLP company. - Lee, Li Sze. (2008)
This is a real-life Business Process Reengineering (BPR) consultancy project conducted in a local firm. The objective was to reengineer the IT Helpdesk processes and monitor its processes using Balanced Scorecard (BSC). Kale’s BPR framework was adopted and the process was mapped using ARIS (Architecture of Information Integrated System) Toolset.